2016
DOI: 10.1097/ico.0000000000001046
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Ocular Manifestations and Visual Outcomes in Patients With Herpes Zoster Ophthalmicus

Abstract: A substantial proportion of patients with HZO were <60 years old in this study. The absence of zoster vaccination across the study cohort was noteworthy. Keratitis was the main reason for poor visual outcome in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 25 publications
1
42
0
2
Order By: Relevance
“…As to other studies, Szwto et al also found that conjunctivitis was the most common ocular manifestation. 21 Our univariate analysis established a significant correlation between HIV infection and ocular involvement in HZO, but not for diabetes mellitus. Nevertheless, HIV infection did not have a significant association with ocular involvement in HZO after adjustment by the multivariate analysis.…”
Section: Discussionmentioning
confidence: 64%
“…As to other studies, Szwto et al also found that conjunctivitis was the most common ocular manifestation. 21 Our univariate analysis established a significant correlation between HIV infection and ocular involvement in HZO, but not for diabetes mellitus. Nevertheless, HIV infection did not have a significant association with ocular involvement in HZO after adjustment by the multivariate analysis.…”
Section: Discussionmentioning
confidence: 64%
“…Herpes zoster ophthalmicus (HZO), a condition that affects the ophthalmic division of the trigeminal nerve, is caused by reactivation of latent varicella zoster virus; about 10% of people with varicella zoster infections experience HZO . Over the past decade, the number of emergency department presentations by people with herpes zoster in Australia has increased by 2–6% per year, and the number of people with herpes zoster managed in general practice has almost doubled …”
mentioning
confidence: 99%
“…The conjunctiva was closed using 6-0 polyglactin in a simple continuous pattern. Median (range) surgical time for both eyes was 35 (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) min. Neomycin-polymyxinbacitracin ophthalmic ointment was placed in both eyes twice daily for 5-6 days following implant placement.…”
Section: Experimental Designmentioning
confidence: 99%
“…While some indications for use may differ between the 2 species, famciclovir is prescribed for herpetic keratitis in both species. [26][27][28][29][30][31] In this study, we assessed the safety and tolerability of delivering penciclovir at the corneal surface from a nonbiodegradable subconjunctival implant as a means to overcome concerns regarding systemic drug toxicity and patient compliance. This implant was previously used to deliver acyclovir subcutaneously to mice inoculated with HSV-1, 32 and, in in vitro experiments, it has been demonstrated to release penciclovir and suppress replication of FHV-1.…”
mentioning
confidence: 99%